PENGARUH JOB INVOLVEMENT DAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SINAR KARYA DUTA ABADI - ROSYIDA, FATIA (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to examine and analyze the effect of job involvement and locus of control to employee job satisfaction at PT. Sinar Karya Duta Abadi. Data obtained from the results of questionnaires and interviews. Samples in this study were 87 respondents taken with Proportionate Stratified Random Sampling. Technique of collecting data used is questionnaire technique which disseminated directly to the respondent in this case is employee PT. Sinar Karya Duta Abadi. Data analysis techniques using PLS (Partial Least Square). In addition, this study uses Likert scale as a measurement scale. The results of this study indicate job involvement and locus of control affecting job satisfaction. Keywords : Job Involvement, Locus of Control, Job Satisfaction